Case report: Pellagra presentation with dermatitis and dysphagia - Mengistu, Segenet Bizuneh; Ali, Iman; Alemu, Hiwot; Melese, Endalkachew Belayneh (Frontiers in Medicine, 2024)
Pellagra is a disorder due to a deficiency of niacin or tryptophan manifested by characteristic dermatitis on sun-exposed areas of the skin. Gastrointestinal involvement is common, presenting with glossitis, stomatitis, and diarrhea. Neurologic symptoms can occur with some patients experiencing dementia, anxiety, depression, tremors, hyporeflexia, and encephalopathy in severe cases. We present the case of a woman with hyperpigmentation and hyperkeratosis on sun-exposed areas of the skin and progressive dysphagia. Notably, she did not report diarrhea or any neurologic or psychiatric symptoms. Her presentation was most consistent with pellagra, and niacin supplementation was initiated and led to recovery. This case report highlights dermatitis and dysphagia, the sole gastrointestinal manifestation, can be the only symptoms in patients with pellagra, and a high index of suspicion in dermatologic settings is required to diagnose and treat this fatal condition promptly.